Proposal for developing the performance of Libyan universities in the light of the concept of the learner organization (Albayan Scientific Journal, 2023)
The study aimed to develop a proposed vision to the development of the institutional performance of Libyan universities, in the light of the concept of learning organization, and for improve the way performs its work, and its assigned tasks, enables it to deal with developments and changes, and to increase its production efficiency, the study relies on the descriptive approach, previous studies related to the subject of the study were surveyed, which enabled to present a proposed vision for developing the performance of the administrative staff in Libyan universities in the light of the concept of the educated organization.